Maintenance laws and illegitimate children in Malaysia / Sridevi Thambapillay and Jal Zabdi Mohd Yusoff - Thambapillay, Sridevi; Mohd Yusoff, Jal Zabdi (Faculty of Administrative Science and Policy Studies, 2012)
Since its independence in 1957, our nation has progressed tremendously in various fields such as science, technology and infrastructure. However it is disheartening to note that although our society at large has reaped the benefits of the nation’s developments, the same cannot be said about all segments of the society. One particular category in our society which is still left behind is the illegitimate children. Various laws have been passed to protect and safeguard the rights and interests of children in Malaysia. In fact, Malaysia has signed and ratified with reservations the United Nations Convention on the Rights of the Child (CRC). Nevertheless mere existence of laws does not guarantee that the rights and interests of children, especially illegitimate children are protected. Thus, the purpose of this paper is to examine the maintenance laws concerning non-Muslim children in order to see if their rights and interests are adequately protected and further to suggest reforms to these laws.